IMPACT OF ELECTRONIC MEDICAL RECORD (EMR) SYSTEMS ON IMPROVING CLINICAL DOCUMENTATION AND CODING ACCURACY - Ibrahim Mohammed N Almojally, Bader Fahad Hajed Alharbi, Saif Saad Almutairi, Fathiyaha Mahmoud Somail, Kholood Yehya Hassan Mohagab, Nouf Fahad Mohammad Alkharji; Abdulamuhesn Fahad Mohammad Alkharji, Nadiya Lutify Hashim Atefy, Manal Abdulrhman Thafer Aldossary, Yahya Mohammad Mashee, Reem Hilal Break Al-Otaibi; Abdallah German Alamri, Abdullah Saeed Abdullah Alghamdi, Bader Qaryan Alruwaili, Turki Saed A Alghamdi (Chelonian Research Foundation, 2022)
Electronic health records (EHRs) are being used more and more, however there are issues with their quality. There has been an attempt to address the causes of low-quality EHR documentation. Prior systematic evaluations evaluated the efficacy of interventions in the context of outpatient care or paper recording. This systematic review set out to evaluate the efficacy of interventions aimed at enhancing EHR documentation in inpatient settings. Extensive inclusion/exclusion criteria served as the foundation for the development of a search strategy. Reference lists, gray literature, and four databases were looked through. Data extraction was done using a REDCap data capture form, and a bespoke tool was utilized to evaluate the quality of the study. Data were semiquantitatively and narratively evaluated and synthesized. The most effective interventions were education and the introduction of a new EHR reporting system, as shown by the noticeably better EHR documentation. Measuring the impact of interventions and the quality of EHR documentation was made challenging by the heterogeneity of outcomes, document types, EHR users, and other variables. On the other hand, the major intervention strategy of using education was in line with previously published research in related fields. Standardization is necessary since the interventions used to improve EHR documentation are quite inconsistent. This innovative field of study needs to be given more attention in order to enhance provider-to-provider communication and make data exchange between institutions and nations easier. Keywords: inpatient, intervention, quality improvement, documentation, electronic health records